LYSOZYME-INDUCED NEPHROPATHY IN CMML: A RARE BUT SIGNIFICANT COMPLICATION REQUIRING EARLY RECOGNITION AND INTERVENTION - Alfadil Haroon; Mohamed Kindawi; Ahmed S Alotaibi; Ali Debsan Alahmari; Hazzaa Alzahrani; Mansour Alfayez; syed Osman Ahmed (Hematology, Transfusion and Cell Therapy, 2025)
Background: CMML is a clonal hematopoietic disorder with features of myelodysplasia and myeloproliferation, characterized by monocytosis. Monocytes secrete lysozyme, a cationic protein filtered by the glomerulus and reabsorbed in proximal tubules. Excess lysozyme accumulation causes tubular injury, leading to Lysozyme-Induced Nephropathy (LyN). Case 1: A 72-year-old male with CMML that transformed into AML with a TP53 mutation. Laboratory results showed WBC 9 × 10⁹/L, Hb 80 g/Platelets 139 × 10⁹/L, and creatinine 162 µmoL/L. Additional findings included Na 129 mmoL/L, Cl 97 mmoL/L, Mg 0.51 mmoL/L, PO4 1.50 mmoLL, and 24-hour urine protein of 1.20 g/L. LyN was suspected and confirmed with a lysozyme level of 117 mcg/mL (2.7‒9.4). He was treated with Azacitidine and Venetoclax, achieving CR and normal renal function. Case 2: A 60-year-old male with CMML initially presented with a creatinine level of 139 µmoL/L, Na 130 mmoL/L, K 2.6 mmoL/L, normal Magnesium, and a lysozyme level of 153 mcg/mL. His creatinine normalized with prednisone. He progressed to AML after six cycles of Azacitidine and later received four cycles of Venetoclax, achieving CR. Unfortunately, he passed away 18-months post-diagnosis due to pneumonia and pulmonary hemorrhage. Case 3: A 57-year-old female with CMML transformed into AML underwent MSD SCT but relapsed after five months. She initially achieved CR with Aza-Ven, followed by DLI, but relapsed again after four years. She was unresponsive to Aza-Ven but improved with palliative cytarabine. Initially, she had AKI due to TLS, which improved with chemotherapy. During her last relapse, she had creatinine of 154 µmoL/L, lysozyme levels 124 mcg/mL and electrolyte imbalances. Her renal function significantly improved after cytarabine injections. Discussion/Conclusion: Most frequent renal complications in CMML are LyN (56%) and renal infiltration by the CMML with incidence of AKI (34.9%) and CKD (7.6%). LyN is a rare and poorly understood complication of CMML. Filtered lysozyme accumulates in the renal cortex, causing severe hypokalemia via kaliuresis or direct tubular injury, potentially leading to kidney failure. In our patient CMML treatment, hydration and steroids restored kidney function. LyN in CMML necessitates early recognition and intervention to improve renal outcomes. Further research is needed to optimize treatment strategies.